Design of smart structures for wind turbine blades - Supeni, Eris Elianddy; Epaarachchi, Jayantha Ananda; Islam, Md Mainul; Lau, Kin Tak (2012)
The wind turbine blade is a very important part of the rotor. Extraction of energy from wind depends on the design of the blade. The advancement of fibre composite materials have provided the best solutions to overcome inefficiencies caused by traditional materials used in wind turbine construction. At present, the majority of wind turbine blades are constructed with glass fibre reinforced plastic (GFRP). The use of composite materials eventually have solved some of the problems associated with efficient operation of horizontal axis wind turbines (HAWTs) such as gravitational forces due to weight but there are other unresolved problems such as long term material property degradation, local shape deformation of the profile of the wind turbine blades etc. This project aims to address the adverse structural response of the blade profile with the variation of operational parameters such as wind velocity and material properties on blade’s performances. For this reason, the shape memory alloy (SMA), which is Nitinol (NiTi) has been embedded in the blade to alleviate the load. A parametric blade model utilising the Abaqus finite element program has been developed to efficiently predict the deflection of the blade. Result obtained from Abaqus is compared with the current experimental work. It was found that the numerical model developed in FEA agreed relatively well with the experimental work, thus validating underlying assumptions.